SEMIOTIKA VISUAL LOGO UNIVERSITAS ICHSAN GORONTALO - Siska Udilawaty; Kemal Ilham Pramudya; Wicandri Pasambuna (Pixel :Jurnal Ilmiah Komputer Grafis, 2023)
This research uses qualitative methods with semiotic analysis from Roland Barhes. Semiotics is a method for analyzing signs to find meaning in social and cultural phenomena. The aim of this research is to find out what visual meaning is contained in the Ichsan Gorontalo University logo which is used as an agency identity in terms of denotation, connotation and myth. Corporate identity is a reflection of the vision and mission which are visualized through the logo. This research uses a qualitative descriptive method, namely the data collected is in the form of words and images. With the right logo, the message regarding the company's desired identity can be represented effectively. Data collection techniques use documentation/library techniques and observation. The results of this research will explain the meaning of the Ichsan Gorontalo University logo which has signs/symbols and colors that will be differentiated based on Roland Barthes' approach.